PERLINDUNGAN HAK-HAK ANAK SEBAGAI AKIBAT DARI PERCERAIAN (STUDI KASUS DI PENGADILAN AGAMA KABUPATEN KEDIRI DALAM PERKARA CERAI TALAK) - FH, Suharto (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH; Vol 2 No 01 (2022): Januari-Mei 2022DO - 10.32503/ammer.v2i01.2430, 2022)
The purpose of this study was to determine the consequences and legal application of PERMA Number 3 of 2017 on women's rights and children's rights in the jurisdiction of the Kediri Regency Religious Court. The empirical method is used in this study to see the law in a real sense and to examine it directly using field research methods and techniques. The results of this study indicate that the real application of PERMA No. 3 of 2017 judges at the Kediri Religious Court agreed that in deciding cases of marital disputes, the rights of the wife after the divorce who was divorced by her husband if they wanted to obtain their rights there must still be a request first. The judge cannot suddenly decide on an unsolicited decision and of course the judge takes into account the evidence, both from witness statements and other evidence (related to the rights of mut`ah and iddah maintenance). If the woman who is divorced by her husband wants to get her post-divorce rights such as iddah living, madliyah living, mut'ah living, hadhanah rights and child support, the divorced woman can file a counterclaim. file a divorce suit and want to obtain their rights, then the lawsuit must include a request for their rights.